Sistem Informasi Desa Tirta Jaya Berbasis Web - Fortuna, Dewi (mijournal.org, 2024)
Tirta Jaya Village is one of the villages in Bajuin District, Tanah Laut Regency, South Kalimantan Province. It has an area of approximately 550 hectares. Tirta Jaya Village consists of 2 hamlets covering 12 RT. Tirta Jaya Village has a population of approximately 2,681 people consisting of 1,344 men and 1,337 women with a population density of 487/km2 and a total of 876 heads of families (KK). Tirta Jaya uses a word processing application. Not all village officials have computer skills to create uniform correspondence, which makes village administrative services very dependent on certain administrative staff. Obstacles in administrative services require the development of an Information ”yste’ that can assist the administrative service process in Tirta Jaya Village. It is hoped that the existence of this information system will make it easier for village officials to serve the population and overcome the weaknesses of manual administration, especially in the process of writing correspondence. Based on the problems above, a Web-based Tirta Jaya Village Information System was designed using the Codeignite framework, the system design used UML and implemented a database using MySQL